Causes of acute hospitalization in adolescence: burden and spectrum of HIV-related morbidity in a country with an early-onset and severe HIV epidemic: a prospective survey. - Rashida A Ferrand; Tsitsi Bandason; Praise Musvaire; Natasha Larke; Kusum Nathoo; Hilda Mujuru; Chiratidzo E Ndhlovu; Shungu Munyati; Frances M Cowan; Diana M Gibb; Elizabeth L Corbett (PLoS Medicine)
Background Survival to older childhood with untreated, vertically acquired HIV infection, which was previously considered extremely unusual, is increasingly well described. However, the overall impact on adolescent health in settings with high HIV seroprevalence has not previously been investigated. Methods and findings Adolescents (aged 10-18 y) systematically recruited from acute admissions to the two public hospitals in Harare, Zimbabwe, answered a questionnaire and underwent standard investigations including HIV testing, with consent. Pre-set case-definitions defined cause of admission and underlying chronic conditions. Participation was 94%. 139 (46%) of 301 participants were HIV-positive (median age of diagnosis 12 y: interquartile range [IQR] 11-14 y), median CD4 count = 151; IQR 57-328 cells/microl), but only four (1.3%) were herpes simplex virus-2 (HSV-2) positive. Age (median 13 y: IQR 11-16 y) and sex (57% male) did not differ by HIV status, but HIV-infected participants were significantly more likely to be stunted (z-score<-2: 52% versus 23%, p<0.001), have pubertal delay (15% versus 2%, p<0.001), and be maternal orphans or have an HIV-infected mother (73% versus 17%, p<0.001). 69% of HIV-positive and 19% of HIV-negative admissions were for infections, most commonly tuberculosis and pneumonia. 84 (28%) participants had underlying heart, lung, or other chronic diseases. Case fatality rates were significantly higher for HIV-related admissions (22% versus 7%, p<0.001), and significantly associated with advanced HIV, pubertal immaturity, and chronic conditions. Conclusion HIV is the commonest cause of adolescent hospitalisation in Harare, mainly due to adult-spectrum opportunistic infections plus a high burden of chronic complications of paediatric HIV/AIDS. Low HSV-2 prevalence and high maternal orphanhood rates provide further evidence of long-term survival following mother-to-child transmission. Better recognition of this growing phenomenon is needed to promote earlier HIV diagnosis and care.